Report of the Second Satellite Symposium on Ultrasound in Schistosomiasis - Joachim Richter; Ana Lúcia Coutinho Domingues; Cristina Hueb Barata; Áluízio Prata; José Roberto Lambertucci (2001)
A group of experts on schistosomiasis and ultrasonography discussed the experiences and results obtained with the Niamey-Belo Horizonte Protocol on Ultrasonography in Schistosomiasis. A series of recomendations about qualitative and quantitative data obtained by ultrasound in studies performed in Africa and Brazil are presented. Imunological, genetic and epidemiological studies must rely on ultrasound for the identification of patients with periportal thickening/fibrosis.